The Application Of Integrated Marketing In Emory Style - Eva Noorliana; Golan Hasan (Universitas Internasional Batam, 2023)
Social media is one of the most effective and efficient marketing method nowadays. Planning for creating content that suits the market for each social media such as Tiktok, Instagram, and Facebook is important in order to expand brand awareness and increase customer loyalty. Integrated marketing is a marketing system that prioritizes marketing planning for various media. The implementation of integrated marketing in Emory Style aims to tailor the content so that it can enter the market according to the target of each social media, which can be seen through the insights of each social media. the output of implementing integrated marketing in the future can become the next benchmark for a content marketing system in Emory Style.